Health status of workers approximately 60 years of age and the risk of early death after compulsory retirement: A cohort study. Issue 1 (27th September 2019) - Sakurai, Masaru; Ishizaki, Masao; Miura, Katsuyuki; Nakashima, Motoko; Morikawa, Yuko; Kido, Teruhiko; Naruse, Yuchi; Nogawa, Kazuhiro; Suwazono, Yasushi; Nogawa, Koji; Nakagawa, Hideaki
Abstract: Objectives: The increasing number of working elderly people has enhanced the importance of workplace health promotion activities. We investigated the association between the health status of workers approximately 60 years of age and the risk of all‐cause mortality after compulsory retirement in Japan. Methods: The 2026 participants (1299 males and 727 females) had retired from a metal‐products factory at ≥60 years of age. Baseline health examinations were conducted at 60 years of age and included questions about medical history and lifestyle factors; the participants also underwent a physical examination. The participants were followed up annually by mail for an average of 7.4 years. The association between health status at age 60 years and the risk of all‐cause mortality was assessed by Cox proportional hazards regression analysis. Results: During the study, 71 deaths were reported. The age‐ and sex‐adjusted hazard ratio (HR [95% confidence interval]) for all‐cause mortality was higher for males (HR, 3.41 [1.73‐6.69]) compared with females, participants with a low body mass index (<18.5 kg/m 2 ; HR 3.84 [1.91‐7.73]) compared with normal body weight, smokers (HR, 2.63 [1.51‐4.58]) compared with nonsmokers, and those with three or more of four metabolic abnormalities (obesity, high blood pressure, dyslipidemia, and glucose intolerance) (HR 2.29 [1.04‐5.02]) compared with no metabolic abnormalities. The associations were unaffected by adjustment for these factors. Conclusion: Maintenance of an appropriate body weight, smoking cessation, and elimination of metabolic syndrome are required for older workers to prevent early death after retirement.